Behavioral Intention Mahasiswa dalam Menggunakan QRIS Sebagai Alat Pembayaran Digital Dengan Pendekatan UTAUT 2 - Rotzami Rotzami; Elfadhli Elfadhli; Izzati Tiara Ramadhani; Fatimah Setia Wardhani; Revi Candra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The research aims to determine the behavioral intention of students in using QRIS as a digital payment tool with the UTAUT 2 approach. The type of research used is field research with quantitative methods. The data collection technique used is a questionnaire by distributing questionnaires via google form to respondents. Sampling was 82 respondents who used QRIS from 119 students who became the population determined by purposive sampling technique. The results showed that partially, hedonic motivation and habit affect students' behavioral intention in using QRIS, while performance expectancy, effort expectancy, social influence, facilitating conditions, and price value have no effect on students' behavioral intention in using QRIS. Simultaneously, the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit affect the behavioral intention of students in using QRIS as a digital payment tool with an influence level of 78.9%